The effect of different boron compounds on nutrient digestibility, intestinal nutrient transporters, and liver lipid metabolism - Sahin, Emre; Orhan, Cemal; Erten, Fusun; Sahin, Fikrettin; Şahin, Nurhan; Şahin, Kazım (Tubitak Scientific & Technological Research Council Turkey, 2023)
Background/aim: Gastrointestinal health is essential for maintaining a healthy lifestyle. Improving nutrient absorption and energy metabolism are the critical targets for intestinal health. This study aimed to determine the effects of different boron (B) derivatives on nutrient digestibility, intestinal nutrient transporters, and lipid metabolism in rats.Materials and methods: Twenty-one rats were allocated to three groups (n = 7) as follows: (i) Control, (ii) Sodium pentaborate pentahy-drate (SPP), and (iii) boric acid (BA). The rats were fed a chow diet (AIN-93M) and supplemented with 8 mg/kg elemental B from SPP (45.2 mg/kg BW) and BA (42.7 mg/kg BW) via oral gavage every other day for 12 weeks. The nutrient digestibility of rats in each group was measured using the indigestible indicator (chromium oxide, Cr2O3, 0.20%). At the end of the experiment, animals were decapitated by cervical dislocation and jejunum, and liver samples were taken from each animal. The nutrient transporters and lipid-regulated tran-scription factors were determined by RT-PCR.Results: The nutrient digestibility (except for ash) was increased by SPP and BA supplementation (p < 0.05). SPP and BA-supplemented rats had higher jejunal glucose transporter 1 (GLUT1), GLUT2, GLUT5, sodium-dependent glucose transporter 1 (SGLT1), fatty acid transport protein-1 (FATP1), and FATP4 mRNA expression levels compared to nonsupplemented rats (p < 0.0001). BA-supplemented rats had remarkably higher peroxisome proliferator-activated receptor gamma (PPAR?) levels than nonsupplemented rats (p < 0.0001). In contrast, sterol regulatory element-binding protein 1c (SREBP-1c), liver X receptor alpha (LxR-a), and fatty acid synthase (FAS) levels decreased by SPP supplementation compared to other groups (p < 0.05).Conclusion: SPP and BA administration enhanced nutrient digestibility, intestinal nutrient transporters, and liver lipid metabolism in rats.
Keywords: Boron; energy metabolism; GLUTs; nutrient transporters; PPAR & gamma;